Dhaka City Food System Profile - Islam, Md. Sahidul (CGIAR System Organization, 2024)
The countries and cities in CGIAR target regions are grappling with challenges posed by rapid urbanization and are seeking technically robust, equitable, and scalable solutions within the agrifood sector. Major challenges for agrifood initiatives in urban and peri-urban areas include unhealthy diets and restricted access to nutritious food for the urban poor, food safety and waste reduction, pollution, environmental degradation, the impacts of climate change, and a lack of visibility and support within the urban policy, governance, and investment frameworks.